FACTORS AFFECTING THE PREVENTION OF CORRUPTION USING FRAUD HEPTAGON APPROACH - Hendi Prihanto (Moestopo International Review on Social, Humanities, and Sciences, 2021)
This study aims to obtain evidence of the factors affecting the prevention of corruption in Indonesia by using the fraud Heptagon approach by analyzing the factors causing corruption through organizational culture, leadership, code of ethics, information technology, and governance as intervening variables. The population of the study is government agencies such as ministries, high state institutions, local governments, and other government organizations, obtained randomly through several activities of government agencies such as surveys and coordination meetings using google form and paper-based questionnaires. The results of the study show that information technology has a direct and significant effect on preventing corruption, while organizational culture and code of ethics has a significant indirect effect on good governance.